Analisis Turbin Air Sebagai Alternatif Pembangkit Tenaga Listrik Di Pedesaan - Muhammad Halil; Niharman Niharman (MAJALAH TEKNIK SIMES, 2022)
In an autonomy region era which is signed with appearance many new district ( Kabupaten ) is in order to faster the increasing economic country society . This program should be supported with an existence of electric power The fact that electric power isn't enough for all society especially in the country. It could be understood because generally the distance between a country is far enough and a few number of people in village . All of that make a big invest. Amount complex, the electric power from PLN far from enough. In the village is existence potential water power; nature water fall and irrigation canal that have 2.5 meters height and 250 liter's/second quantities. If two of potential water power could be exist all years long , it can be utilized to move turbine as a micro hydro electric power generator that very potential' in small village.